2011
DOI: 10.1039/c1ob05583f
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent interaction and selectivities in selectin binding of functionalized gold colloids decorated with carbohydrate mimetics

Abstract: Colloidal gold particles with functionalized organic shells were applied as novel selectin binders. The ligand shell was terminated with different monocyclic carbohydrate mimetics as simplified analogs of the sLe x unit found in biological selectin ligands. The multivalent presentation of the sulfated selectin binding epitopes on the gold particles led to extremely high binding affinities towards L-and P-selectin and IC 50 values in the subnanomolar range. Depending on the ring size of the sulfated carbohydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 30 publications
2
23
0
1
Order By: Relevance
“…The polysulfation of the presented carbohydrate mimetics proved to be the most demanding step of the synthesis requiring many attempts and optimizations to find a suitable and reasonably reproducible procedure. Since other sulfation methods such as SO 3 ∙pyridine [35] provided unsatisfactory results an excess of SO 3 ∙DMF [13,36] was used as sulfating agent and the resulting sulfuric acid monoesters (in a mixture with an excess of the sulfating reagent) were directly converted into the corresponding sodium salts using a 1 M solution of sodium hydroxide. Subsequent purification by dialysis against water should afford the desired pure polysulfated compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polysulfation of the presented carbohydrate mimetics proved to be the most demanding step of the synthesis requiring many attempts and optimizations to find a suitable and reasonably reproducible procedure. Since other sulfation methods such as SO 3 ∙pyridine [35] provided unsatisfactory results an excess of SO 3 ∙DMF [13,36] was used as sulfating agent and the resulting sulfuric acid monoesters (in a mixture with an excess of the sulfating reagent) were directly converted into the corresponding sodium salts using a 1 M solution of sodium hydroxide. Subsequent purification by dialysis against water should afford the desired pure polysulfated compounds.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds and their conjugates were prepared to be examined as selectin inhibitors. There we have found that sulfated aminopyrans connected by amide bonds to gold nanoparticles are highly potent inhibitors of L- and P-selectin with IC 50 values in the subnanomolar range [1213]. These lectins are crucial in the inflammatory process [1418] and hence compounds inhibiting their activity are of interest as potential therapeutics [1923].…”
Section: Introductionmentioning
confidence: 99%
“…AuNP core dimension and shape are important parameters to take into consideration for the multivalent carbohydrate presentation [5153]. In fact, a denser ligand packing can be obtained when NP dimensions are bigger and the curvature radius is reduced.…”
Section: Reviewmentioning
confidence: 99%
“…Subsequently we investigated modifications and synthetic applications of 1,2-oxazines 3 including the preparation of seven-membered N,O-heterocycles by ring enlargement [5], functionalization of the enol ether unit [611], and N,O-cleavage reactions leading to amino alcohols [8,10,12], pyrroles [13] or α,β-unsaturated β-alkoxy-γ-amino-aldehydes and ketones [14]. In this context, a series of publications of our group reported on syntheses of carbohydrate mimetics [1520] that are based on aminopyrans, aminooxepanes or other aminopolyols and that were examined for example as ligands of L- and P-selectin [2122]. We previously reported the synthesis of enantiopure 1,2-oxazin-4-yl nonaflates and phosphates starting from precursors of type 3 and their conversion into differently C-4-substituted products employing palladium-catalyzed cross-coupling reactions [23].…”
Section: Introductionmentioning
confidence: 99%